Large‐scale production of extracellular vesicles: Report on the "massivEVs" ISEV workshop. Issue 10 (25th October 2022) - Paolini, Lucia; Monguió‐Tortajada, Marta; Costa, Marta; Antenucci, Fabio; Barilani, Mario; Clos‐Sansalvador, Marta; Andrade, André Cronemberger; Driedonks, Tom A. P.; Giancaterino, Sara; Kronstadt, Stephanie M.; Mizenko, Rachel R.; Nawaz, Muhammad; et al.
Abstract: Extracellular vesicles (EVs) large‐scale production is a crucial point for the translation of EVs from discovery to application of EV‐based products. In October 2021, the International Society for Extracellular Vesicles (ISEV), along with support by the FET‐OPEN projects, "The Extracellular Vesicle Foundry" (evFOUNDRY) and "Extracellular vesicles from a natural source for tailor‐made nanomaterials" (VES4US), organized a workshop entitled "massivEVs" to discuss the potential challenges for translation of EV‐based products. This report gives an overview of the topics discussed during "massivEVs", the most important points raised, and the points of consensus reached after discussion among academia and industry representatives. Overall, the review of the existing EV manufacturing, upscaling challenges and directions for their resolution highlighted in the workshop painted an optimistic future for the expanding EV field.